Postcard-TempleOfVandœuvres-Interior-before1918-BibliothèqueDeGeneveCent... - Auteur inconnu (Wikimedia Commons, 1917)
Notice image issue de Wikimedia Commons. Titre: Postcard-TempleOfVandœuvres-Interior-before1918-BibliothèqueDeGeneveCentreDIconographie. Historical postcard of the interior of the protestant church of Vandœuvres in the canton of Geneva, Switzerland. Photo taken before 1918. From the collections of the Bibliothèque de Genève.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; église; Carte postale